ANALISIS PERMINTAAN ANGKUTAN UMUM GRATIS BAGI PELAJAR DI KABUPATEN TULUNGAGUNG - Priyambodo Priyambodo; Hitapriya Suprayitno (Jurnal Penelitian Transportasi Darat, 2016)
ABSTRACTPoor quality performance of mass public transport services or public passenger car (MPU) has caused it being abandoned by public. The public prefer to use private vehicles both two wheel or four wheel vehicles to support their mobility everyday. No exception for the people in Tulungagung district. The number of public passenger car in Tulungagung district recently is about 134 or 0.03% of the total vehicle in Tulungagung district. The purpose of this study is to find out the problems existed related to the transportation used by students in Tulungagung District concerning the characteristics of the distribution of residence students, the distance between home and school of the students, students transportation demand, a new planning route, the number of vehicles need to be provided for free public transport. This study is using qualitative descriptive analysis, analysis of transport demand and stated preference. The results of the study showed that the pattern of distance route between home and schools of the students resembles a nest of spidersand the demand of free public transport for high school students are less than the junior students. To meet the demand of free public transport for students, 253 bus fleet or fleet of 310 MPU are needed. To meet the distribution routes of free public transport for students, the Government of Tulungagung District need to add the number of routes and the fleet up to 60% for North-South lane and East-West lane. In addition, the Local Transport Communications and Informatics as well as local police has to tighten the use of motor cycle raids and encourage the parents and the students to use free public transport. Since 10% of the students are using motorcycle as their transport to school, eventhough they are still under age. The research also found that about 70% of the students who are using free public transport prefer kind of transportation of buses than type colt station, for this Local Transport Communications and Informatics need to consider in providing the number of bus fleet larger than the colt station.ABSTRAKKinerja atau performance pelayanan angkutan umum massal atau mobil penumpang umum (MPU) yang tidak bagus menjadikan MPU yang bersangkutan ditinggalkan oleh masyarakat. Masyarakat lebih suka menggunakan kendaraan pribadi baik roda dua maupun roda empat untuk mobilitas sehari-hari. Tak terkecuali bagi masyarakat di Kabupaten Tulungagung. Saat ini jumlah MPU di Kabupaten Tulungagung hanya 134 atau 0,03 % dari total kendaraan yang ada di Kabupaten Tulungagung. Tujuan dari penelitian ini adalah untuk mengetahui permasalahan terkait transportasi yang digunakan oleh pelajar di Kabupaten Tulungagung yang menyangkut karakteristik persebaran tempat tinggal pelajar, jarak rumah pelajar dengan sekolah, permintaan transportasi pelajar, rencana trayek baru, jumlah kendaraan MPU gratis yang perlu disediakan. Kajian ini menggunakan analisis deskriptif kualitatif, analisis permintaan transportation dan stated preference, hasil penelitian menunjukkan bahwa pola sebaran domisili para pelajar membentuk dan menyerupai sarang laba-laba. Permintaan angkutan umum gratis tingkat SMA lebih sedikit dibandingkan dengan tingkat SMP. Untuk memenuhi permintaan angkutan umum gratis bagi pelajar diperlukan 253 armada bus atau 310 armada MPU. Untuk memenuhi pemerataan trayek angkutan umum gratis bagi pelajar, Pemerintah Kabupaten Tulungagung perlu menambah rute angkutan umum gratis dan armada sampai dengan 60% untuk jalur utara-selatan dan timur-barat. Disamping itu, Dinas Perhubungan Komunikasi dan Informatika serta kepolisian setempat harus memperketat razia penggunaan sepeda motor dan mendorong kepada orangtua murid dan pelajar untuk menggunakan angkutan umum gratis. Karena 10 % pelajar menggunakan kendaraan roda dua untuk pergi dan pulang sekolah, sementara usia mereka masih dibawah umur. Hasil penelitian juga menunjukkan sekitar 70% pelajar yang menggunakan angkutan umum gratis menyukai angkutan umum dengan armada jenis bus daripada armada MPU jenis colt station, untuk itu kepada Dinas Perhubungan Komunikasi dan Informatika perlu mempertimbangkan untuk pengadaan armada bis yang lebih besar dibandingkan dengan armada MPU jenis colt station.